PENGARUH LIKUIDITAS, LEVERAGE, NILAI PASAR DAN INFLASI TERHADAP POFITABILITAS (STUDI PADA PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019). - Mutmaina, Dewi Asyifa; Hajar, Ibnu; Isalman, Isalman; Hatani, La; Taufik, Muhammad (Jurnal Manajemen dan Kewirausahaan, 2021)
This study aims to determine the effect of liquidity, leverage, market value and inflation on the profitability of textiles and garments. The population in this study were 22 companies and the sample in this study was 13 companies which were selected using purposive sampling method. The results of this study indicate that Liquidity has a negative and insignificant effect on Profitability, Leverage has a positive and significant effect on Profitability, Market Value has a positive and significant effect on Profitability, Inflation has a negative and insignificant effect on Profitability.Â